Keefektifan Model Pembelajaran Conceptual Chang Text dalam Mencegah Miskonsepsi Siswa pada Materi Larutan Penyangga - Fauzannur Fauzannur*; Muhammad Hasan; Sulastri Sulastri (Jurnal Pendidikan Sains Indonesia, 2022)
The low interest in learning chemistry is because there are still some students who have different conceptions, resulting in misconceptions. This study aims to determine the level of students' misconceptions about the buffer solution material in the experimental class and control class and the effectiveness of the conceptual change text (CCT) learning model in preventing students' misconceptions about the buffer solution material at SMAN 1 Seulimeum. The method used in this study is a quasi-experimental designed with a posttest only control group design. The sample selection technique was determined with certain considerations because there were only two classes in class XI IPA, so the two classes were used as samples in this study. So the research sample taken was class XI IPA1 and XI IPA2, totaling 30 and 34 students. The instrument used is in the form of multiple-choice diagnostic test questions. The data analysis technique used four tier. The results showed that the level of students' misconceptions on the buffer solution material in the experimental class and control class before applying the learning treatment obtained an average percentage of 31.18 and 31.33. The effectiveness of the CCT learning model can prevent students' misconceptions about the buffer solution material. The results of data analysis prove that after applying the CCT model students' misconceptions decreased with the misconception score only reaching 2.65. The results of the study can be concluded that the CCT model can prevent misconceptions better than the conventional learning model through the direct instruction model